Comparing Different Methodologies Used in Wayfinding Research in Library Facilities - Mandel, Lauren H. (Qualitative and Quantitative Methods in Libraries; Vol 9 No 2 (2020): June 2020 Issue, 2020)
People need to navigate library spaces to access and use library services and resources. People navigate facilities by wayfinding: figuring out where they are and how to get to what they need. The most commonly used methods to research wayfinding in libraries are interviews, task completion, and observation. Each method has strengths and weaknesses, so understanding which methods are most effective for different research purposes is crucial to future research in this area. There does not appear to be a relationship between method chosen and library type, but there is indication that some methods are preferred for different research goals and that multiple methods are preferred over single methods. All methods appear to be efficacious for answering research questions, but multiple method studies appear to be more efficacious than single method studies.